On perceived effectiveness of graphic warning labels willingness to quit of adult smokers in Balangiga, Eastern Samar - Alas, Geraldine Mae A.; Gilles, Jenny Grace R.; Tan, Analyn Grace B.; Pormon, Miah Maye M. (2017)
Cigarette smoking has been prevalent in the Philippines, and one of the leading causes of the death of many Filipinos considering its negative health effect to smokers, to the community and to the environment. In effect, the government implemented policies and regulations to limit the consumption of cigarettes and one of these policies is Republic Act 10643- An Act to Efficiently Instill Health Consciousness through Graphic Health Warnings on Tobacco Products. Given this policy, the study measured the level of willingness to quit among the 120 cigarette smokers in the six barangays of Balangiga, Eastern Samar. Researchers also described the socio-demographic and economic profile, the smoking behaviors, knowledge and perception towards graphic warning labels and determined the factors affecting the willingness to quit among smokers. Data were gathered through personal interviews and were described using descriptive statistics. Most of the respondents were male and only seven were female. Majority were aged 40 years old and above, and have been smoking for more than twenty years. The majority (51%) reported that the graphic warning labels were quite effective; however, 22% still prefer to continue smoking. Four ordinal logistic regressions were done. Regression results presented that hospitalization, perceived graphic effectiveness and the cognitive responses toward the graphic warnings were significant in affecting the willingness to quit of the respondents. Hence, the government should ensure steps in order strengthen and make the graphic warnings more effective in increasing the willingness of the smokers to quit smoking.
Undergraduate thesis (BASS Economics) -- University of the Philippines, Tacloban.